Food Security and Self-Sufficiency in Europe - Silvia Jacková; Ľudmila Dobošová; Mária Kadlečíková; Zuzana Kapsdorferová (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The submitted scientific paper deals with food security and self-sufficiency in Europe in EU-15 and EU-13 countries. The objective of this paper was to evaluate upon the basis of the Global Food Security Index, the overall food security situation in the European Union states. The countries are divided into two groups. The first is composed of fourteen selected states from the EU -15 and the second group is six selected states from the EU-13. In addition to the Food Security Index, the Food Affordability, Food Availability, and the Food Quality and Safety Indexes were also analyzed. The research data were obtained from the authors‘ own research based on the Global Food Security Index Report, and from FAO.